2018
DOI: 10.1200/jgo.2016.006783
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Prevalence of Pain and Its Management in Four Regional Cancer Hospitals in India

Abstract: PurposeMore than 1 million new occurrences of cancer are diagnosed in India annually. Among patients with cancer, pain is a common and persistent symptom of the disease and its treatment. However, few studies to date have evaluated the prevalence of pain and the adequacy of pain management in Indian hospitals. This cross-sectional study aimed to assess the prevalence and sociodemographic patterns of cancer pain and pain management among a sample of inpatients and newly registered outpatients at four large regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…[829] Lower education level was not a significant predictor in our study, but other studies have found lower education to be a significant factor, more so in developing nations. [3031]…”
Section: Discussionmentioning
confidence: 99%
“…[829] Lower education level was not a significant predictor in our study, but other studies have found lower education to be a significant factor, more so in developing nations. [3031]…”
Section: Discussionmentioning
confidence: 99%
“…[39] Even among the patients who reach tertiary level cancer centers, 96% currently do not have proper palliative care access. [40] The existing palliative care system is not enough for cancer patients alone, centers catering to other noncommunicable conditions are fewer. [3638] With the epidemiological transition, the prevalence of noncommunicable diseases (NCDs) are rising, and they will also create a strain on the palliative care system.…”
Section: Palliative Care Provision In Indiamentioning
confidence: 99%
“…[ 4 ] In a study done in four regional cancer centers in India, a total of 88% of patients reported experiencing pain for about 7 days, and approximately 60% reported that their worst pain was severe. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%